Primary pleural serous carcinoma of mullerian origin—Report of a rare case - Shilpi Modi; Deepa Goel (Indian Journal of Pathology and Microbiology)
Mullerian tumor arising from pleura is a rare occurrence and under-reported in medical literature. We hereby present such a case in a 47 years old female who presented with pleural effusion. Pleural biopsy revealed a papillary tumor with mild-to-moderate nuclear atypia. Immunohistochemistry profile with positivity for WT1, Pax8, ER, and PR together with negative mesothelial markers and ruling out primary in female genitalia led us to a diagnosis of primary pleural serous carcinoma of mullerian origin. The patient received paclitaxel and carboplatin chemotherapy and is disease-free till now after 2 years of follow-up.